Optimization of Agility and Emotion Towards Penalty Kick in Athletes Mountain Light Football Academy Kendal - Recoba, Bara Alvaro; Sungkowo, Sungkowo; Permono, Purwono Sidik; Haryono, Sri (Jurnal Abdimas, 2025)
The purpose of this study was to determine 1) the correlation agility towards penalty kicks in Cahaya Gunung Football Academy Kendal athletes. 2) Knowing the emotional correlation towards penalty kicks in Cahaya Gunung Football Academy Kendal athletes, 3) Knowing the correlation between agility and emotional towards penalty kicks in Cahaya Gunung Football Academy athletes. The research used by the author is quantitative research, using the correlational method. The place of implementation of this research is at Cahaya Gunung Football Academy Kendal, with research subjects as many as 24 athletes. The data analysis technique uses multiple regression analysis with a significance level of 5%. The results of the hypothesis test 1 showed a calculated r value of 0.503 > r table (0.05) ( 24 ) ( 0.388 ), it was concluded that there was a significant correlation between agility and penalty kicks in Cahaya Gunung Football Academy Kendal athletes. The results of the hypothesis 2 test show a calculated r value of 0.697 > r table (0.05) ( 24 ) ( 0.388 ), so it can be concluded that there is a significant relationship between emotions and penalty kicks in Cahaya Gunung Football Academy Kendal athletes. The results of the hypothesis 3 test obtained a calculated F result of 13.853 with F table = 3.47, so that the calculated F > F table (13.853 > 3.47) concluded that there was a significant correlation between agility and emotion towards penalty kicks in Cahaya Gunung Football Academy athletes.